Akurasi dalam Mendeteksi Penyakit Kulit Menular menggunakan Gabungan Metode Forward Chaining dengan Certainty Factor - Deosa Putra Caniago; Sumijan (Jurnal Informasi dan Teknologi, 2020)
The skin is the outer protective organ for humans. Skin is the most interacting layer with the environment. Interactions that occur are not always safe against bacteria, viruses, fungi and parasites, so they will cause harm. Poor interactions will result in skin diseases. This skin disease is often considered normal, but can be dangerous and deadly and contagious. Due to the natural conditions and lack of medical personnel, sufferers of skin diseases have problems in examining their skin diseases. So this research was conducted by using an Expert System (Expert System) to help sufferers of skin diseases and help get solutions to these diseases. The solution obtained from the symptoms felt by sufferers. The method used in this study is Forward Chaining (FC) and processed using the Certainty Factor (CF) Method. The results of this study can determine the right initial steps in dealing with infectious skin diseases. So this research is very helpful for sufferers in knowing the type of skin disease, the solution in its prevention and its prevention precisely.